Women Empowerment to Build Entrepreneurship - Karwati, Lilis; Ansori, Ansori; Mulyono, Dinno (Universitas Negeri Semarang, 2018)
Problems in the implementation of women empowerment activities organized by government or community institutions indicate that the number of women is large enough, yet can not be utilized all the potential for development purposes because women can not enjoy life better because of the shackles of cultural sanctions. the theoretical studies developed related to building women through entrepreneurship program is one of the reasons to empower women to be able to create entrepreneurship opportunities. This study was conducted using research and development methods with data collection techniques; literature study, observation, interview, documentation, questionnaire and test. The data are analyzed descriptively, qualitatively and quantitatively. Implementation of activities in Neglasari Village Tasikmalaya. The findings show that the implementation of entrepreneurial activities as an effort to empower women can improve the level of better family economy. The results of this activity can be concluded that the model of empowerment of entrepreneurship women is very effective to improve self-reliance.